SUSTAINABILITY OR FALSE SOLUTION? A CRITICAL VIEW OF CARBON CAPTURE, UTILIZATION, AND STORAGE (CCUS) AND THE FUTURE OF ITS IMPLEMENTATION IN INDONESIA - Muhammad Dhiya Taraki; Riswanda Imawan; Zulmi Zuliansyah (Jurnal Ilmiah Hubungan Internasional Fajar, 2024)
This study aims to evaluate the effectiveness of carbon capture as a carbon emission reduction strategy in the oil and gas sector in Indonesia. In an effort to reduce carbon emissions from the oil and gas industry, the Government of Indonesia through the Ministry of Energy and Mineral Resources (ESDM) has begun to take the development of Carbon Capture Storage (CCS)/ Carbon Capture Utilization and Storage (CCUS) technology seriously. This seriousness can be seen through the creation of 16 CCUS projects that are currently under development. This effort is not only to reduce greenhouse gas emissions, but also so that Indonesia is able to utilize CO2 waste and methane gas to be developed as useful products. This research attempts to examine the application of CCUS as a policy solution towards net zero emission 2060 and the sustainability that Indonesia wants to achieve. Adopting a qualitative approach, this study analyzes sustainability claims in the implementation of CCUS projects. The results show that although CCUS is promoted and considered as a solution to reduce emissions and develop new investments for the state, its presence tends to act more as a greenwashing strategy than as an effective step towards sustainability. In addition, other findings show that the presence of CCUS is actually an obstacle to the green transition efforts that are trying to be achieved. The urgency of this research lies in the effort to see the effectiveness of the CCUS policy which is claimed to be the main way to deliver sustainability policies and Indonesia net zero emission 2060.